Protective sensory loss and foot care practices in a group of diabetic patients attending a medical clinic at the National Hospital Sri Lanka - Gunathilake, H.M.D.R.; Thalawattegedara, C.C.; De Abrew, K.; Sheriff, M.H.R. (My University, 2002)
Peripheral sensory neuropathy is a major risk factor for diabetic foot ulceration. At risk patients need meticulous attention to foot care to prevent complications. To assess the percentage of diabetic patients with protective Sensory loss attending the University Medical Clinic, NHSL, and investigate their foot care practices. Cross-sectional study. Diabetic patients who attended, the University Medical Clinic Caring a 2 month period were interviewed using a pre-tested questionnaire. Foot care practices related to using footwear, washing and inspecting feet, cutting nails, prevention of dry skin, and steps taken after foot ulceration were evaluated. Feet were examined for sensory loss using </07 Semmes Weinstein monofilaments. 60 patients (75% females), mean age 56 years (SD 12), mean duration of diabetes 9.7 years (SD 5.17) were included. 33% had loss of protective sensation in the feet. 50% were asymptomatic. Foot ·ulceration was more common and the amputation rate was higher in patients with sensory loss (p<0.05). Foot care practices were 'very good' (score 81-100%) in 2%, 'good' (66-80%) in 12%, 'average' (51-65%) in 27%, 'poor' (26-50%) in 47% and 'very poor' (0-25%) in 12%. The mean overall score was 46.1 % (SD 17.84). Foot care practices were unrelated to risk level. Patients who had been regularly advised had better practices. Patients need regular advice and motivation to sustain good foot care practices. Promotion of intensive foot care in subjects with protective sensory loss is essential.